All-sky search for long-duration gravitational wave transients in the first Advanced LIGO observing run. (14th February 2018) - Abbott, B P; Abbott, R; Abbott, T D; Abernathy, M R; Acernese, F; Ackley, K; Adams, C; Adams, T; Addesso, P; Adhikari, R X; Adya, V B; Affeldt, C; et al.
Abstract: We present the results of a search for long-duration gravitational wave transients in the data of the LIGO Hanford and LIGO Livingston second generation detectors between S e p t e m b e r 2015 and J a n u a r y 2016, with a total observational time of 49 d . The search targets gravitational wave transients of 10–500 s duration in a frequency band of 24–2048 Hz, with minimal assumptions about the signal waveform, polarization, source direction, or time of occurrence. No significant events were observed. As a result we set 90% confidence upper limits on the rate of long-duration gravitational wave transients for different types of gravitational wave signals. We also show that the search is sensitive to sources in the Galaxy emitting at least ̃10 −8 M ⊙ c 2 in gravitational waves.